Microscopic appearance of healthy teeth, burned-tooth and automobile battery solution soaked tooth for the importance of visum in forensic dentistry - Rozano, Randy; Dardjan, Murnisari; Oscandar, Fahmi (Universitas Padjadjaran, 2013)
Introduction: The hard tissue of the teeth is resistant to heat and acid, so that the teeth have an important role as a material consideration of forensic dentistry. The humans have the same shape of the teeth around one in two billion. The stimuli of burn with high temperature and sour can be change the picture of macroscopic and microscopic tooth. This is the subject of an interesting comparison in the interests of justice and identification of dentistry. Methods: This research was a quasi experiment to analyzed change of microscopic teeth on the hard cases tooth-burning and the case hard acid treatment.The sample used were seven teeth, with details of one normal as a comparison, three teeth burned and three teeth soaked in a solution of water of accu.. Observations were made using the microscope at 40x enlarged on each tooth. The tooth was documented by means of a photographed and compared with healthy teeth. Observing and comparing the microscopic structure and the obtained differences in the teeth and treated with the picture of normal teeth. Results: The results of this study was obtained by observing and comparing the microscopic structure and the obtaineddifferences in the teeth and treated with the picture of normal teeth. Conclusion: The tooth are burned was visible loss of enamel at the cement-enamel junction as a result of the process of carbonization heat exposure so as to cause a breach of micro on the outer layer of the tooth enamel and thinning of dentin tubules, while the teeth are in the soak water accu (strong acid) seen change in color of enamel, micro cracks due to defective enamel and depletion of tubulus dentine and loss of boundary between the cementum and dentine.